2012
DOI: 10.1007/s10765-012-1191-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Halogen Ions on Phase Equilibrium of Methane Hydrate in Porous Media

Abstract: The influences of halogen ions extracted from sodium fluoride, sodium chloride, sodium bromide, and sodium iodide and their concentrations on methane hydrate phase equilibrium conditions in porous media were investigated experimentally using an orthogonal test method at a pressure of 8 MPa. The experimental results showed that the equilibrium temperature of methane hydrate decreased when halogen ions were added. The equilibrium temperature decreased with the increase of halogen ion concentrations. The influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In the past 20 years, researchers have conducted many studies on the hydrate phase equilibrium and reaction kinetics in porous media. However, to date, the effect of porous media on hydrate thermodynamic and kinetic characteristics still is not clear. In 2015, Zang et al reported that one of the key factors causing this issue was the lack of explicit classification of porous media .…”
Section: Introductionmentioning
confidence: 99%
“…In the past 20 years, researchers have conducted many studies on the hydrate phase equilibrium and reaction kinetics in porous media. However, to date, the effect of porous media on hydrate thermodynamic and kinetic characteristics still is not clear. In 2015, Zang et al reported that one of the key factors causing this issue was the lack of explicit classification of porous media .…”
Section: Introductionmentioning
confidence: 99%
“…The detailed procedure can be found in our previous publications . The isochoric method was used to measure the hydrate phase equilibrium conditions, which means the experiments were processed in a constant volume, and there was no mass transfer between the vessel and the environment during the hydrate formation and dissociation process.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used the ionic composition of Tishchenko et al (2005) to calculate the maximum salinity curve, which differed substantially from that of the Nankai Trough (Strasser et al, 2014). The inhibitory effect of different ions on hydrate generation varied (Chong et al, 2017), and the accuracy of the results could be improved by considering the influence on phase equilibrium conditions of low ion concentrations (Yang et al, 2012).…”
Section: Effectiveness Of the Salt Inhibitionmentioning
confidence: 99%